Risk assessment of gently inclined mudstone bedding slope incorporating monitoring information - Mingzhou Bai; Ling Yang; Lixuan Liu; Wanxue Long; Yiming Xiang (Geomatics, Natural Hazards & Risk)
The formation mechanism of gently inclined bedding slopes is complex and difficult to identify, the risk assessment are required. The assessment model is established by using the analytic hierarchy process (AHP) and Fuzzy Comprehensive Evaluation (FCE). Based on the analysis of instability failure modes and influencing factors for gently inclined mudstone bedding highway slopes during the operation period, topography and geomorphology, geological conditions, natural inducements and slope deformation are selected as the evaluation indices, and the corresponding criteria of risk assessment system are established. The weights of evaluation indices are obtained by using AHP, and the measure functions are established to assess single index measurement and synthetic measurement. The weighted average membership degree criterion is adopted to discern the risk grade. The results indicate that the secondary indicators affecting the stability of gently inclined mudstone bedding slopes are modified tangent angle (0.137) and internal friction angle (0.126). This indicates it is necessary to incorporate deformation monitoring information into evaluation indicators, and the risk grade was determined as high risk, which corresponds with actual monitoring data and verifies the reliability of the present method. It provides a novel approach for risk assessment of gently inclined mudstone bedding slopes during the operation period.